Ion conformation and orientational order in a dicationic ionic liquid crystal studied by solid-state nuclear magnetic resonance spectroscopy - Majhi, Debashis (Sci Rep, 2021)
Ionic liquids crystals belong to a special class of ionic liquids that exhibit thermotropic liquid-crystalline behavior. Recently, dicationic ionic liquid crystals have been reported with a cation containing two single-charged ions covalently linked by a spacer. In ionic liquid crystals, electrostatic and hydrogen bonding interactions in ionic sublayer and van der Waals interaction in hydrophobic domains are the main forces contributing to the mesophase stabilization and determining the molecular orientational order and conformation. How these properties in dicationic materials are compared to those in conventional monocationic analogs? We address this question using a combination of advanced NMR methods and DFT analysis. Dicationic salt 3,3′-(1,6-hexanediyl)bis(1-dodecylimidazolium)dibromide was studied. Local bond order parameters of flexible alkyl side chains, linker chain, and alignment of rigid polar groups were analyzed. The dynamic spacer effectively “decouples” the motion of two ionic moieties. Hence, local order and alignment in dicationic mesophase were similar to those in analogous single-chain monocationic salts. Bond order parameters in the side chains in the dicationic smectic phase were found consistently lower compared to double-chain monocationic analogs, suggesting decreasing contribution of van der Waals forces. Overall dication reorientation in the smectic phase was characterized by low values of orientational order parameter S. With increased interaction energy in the polar domain the layered structure is stabilized despite less ordered dications. The results emphasized the trends in the orientational order in ionic liquid crystals and contributed to a better understanding of interparticle interactions driving smectic assembly in this and analogous ionic mesogens.